Qualitative Study of Sexual Violence Mapping at Islamic Religious Universities, Nusa Tenggara Barat - Tuti Harwati; Dwi Widarna Lita Putri (Khazanah Sosial, 2024)
This article discusses the pattern of sexual violence that occurs at Islamic Religious Universities, Nusa Tenggara Barat (NTB). The benefit of this research is providing information about patterns of sexual violence that occur at Islamic Religious Universities, NTB so that it can be used as material for research. Policy for campuses under other religious ministries or the Minister of Research, Technology and Higher Education. The aim is to find patterns of sexual violence that occur at Islamic Religious Universities, NTB. The research methodology is qualitative with a case study approach because the research object is in the form of symptoms which are easier to explain thoroughly by describing words. Case studies are used to investigate and understand an incident or problem in the form of sexual violence that occurred at Islamic Religious Universities, NTB, then processed to obtain a solution in the form of preventing and handling cases of sexual violence. This research found perpetrators of sexual violence at Islamic Religious Universities, NTB is dominated by men. The forms of sexual violence experienced include verbal, physical sexual violence and through information and communication technology. Of the three forms of sexual violence, verbal sexual violence is the most common form of violence compared to other forms of sexual violence.